Little women. - Alcott, Louisa M,. (London Puffin Books, 1953)
Chronicles the humorous and sentimental fortunes of the four March sisters as they grow into young women in nineteenth-century New England.
Keywords: March family (Fictitious characters) -- Juvenile fiction; Family. -- New England -- Juvenile fiction; Sisters -- New England -- Juvenile fiction; New England -- Fiction; Domestic fiction